2013
DOI: 10.1016/j.exer.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

miRNA and mRNA expression profiling identifies members of the miR-200 family as potential regulators of epithelial–mesenchymal transition in pterygium

Abstract: The current study investigates whether microRNA (miRNA) regulators of epithelial-mesenchymal transition (EMT), tissue fibrosis, and angiogenesis are differentially expressed in human primary pterygium. Genome-wide miRNA and mRNA expression profiling of paired pterygium and normal conjunctiva was performed in the context of conventional excision of pterygium with autotransplantation of conjunctiva (n=8). Quantitative real time polymerase chain reaction (qRT-PCR) was used to validate the expression of key molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 52 publications
3
59
0
Order By: Relevance
“…It also has been shown that miR-29 plays a critical role in the pathology of eye diseases, including pterygium 21 , cataract 22 , glaucoma 23–25 and FECD 26 . In trabecular meshwork cells, miR-29 is a critical regulator of ECM expression 23–25 .…”
Section: Introductionmentioning
confidence: 99%
“…It also has been shown that miR-29 plays a critical role in the pathology of eye diseases, including pterygium 21 , cataract 22 , glaucoma 23–25 and FECD 26 . In trabecular meshwork cells, miR-29 is a critical regulator of ECM expression 23–25 .…”
Section: Introductionmentioning
confidence: 99%
“…In this hypothesis, epithelial cells transform into abnormal fibroblasts which then mediate the changes that result in pterygium. 35 It is surprising that neither Chien et al 65 nor Engelsvold et al 66 reported miR-215 to be of importance. One reason would be the heterogeneity of tissues involved and the lack of same eye controls in other studies.…”
mentioning
confidence: 99%
“…This microRNA has not been described in the context of tissue fibrosis. Yet, other studies found it to be associated with EMT processes [31]. It has also been described to be associated with stemness and invasiveness of non-small cell lung cancer [32].…”
Section: Discussionmentioning
confidence: 99%